Counseling for the realization of Anti-HIV serology among pregnant women - Neves, Fátima Regina de Almeida Lima (2009)
Introduction: due to the large number of cases of aids among women and the consequent increase in mother-to-child transmission, the city of Ribeirão Preto - SP established in 1996 the “Protocol to offer of anti-HIV testing in prenatal advice on pre and post-test” in all core network of health. Objective: to discuss the process of counseling in the perception of nurses and doctors gynecologists. Methods: the concept of vulnerability was used as theoretical reference and Analisis of Prose, André (1993), was used as the methodology post-execution of focus groups. The topic explored was counseling. Results: we extracted two thematic groups: counseling and work process. In counseling emerged the sub themes: the voluntary character of HIV test; perception of risk; breaking the chain of transmission and feelings facing the HIV/aids. At the core thematic work process, were generated the sub themes: planning of actions in units of health and human resources in health. We took into account the multiple dimensions of the practice of counseling based on the existing care model and subjectivity of the actors involved. Conclusion: despite all the progress in scientific and technological fields, aids remains a disease that mobilizes many feelings, such as fear, confusion, misinformation and discrimination. The need to prioritize cross-cutting themes such as sexuality and drugs in the training of these professionals was evident. To improve the quality of care using the strategy of counseling necessary with reflection and analysis of practical counseling, from the perspective of the relationship of health professional-patient, aimed at raising awareness of the need to change in the way of doing the work in health.